Dallas Cowboys - Roselius, J Chris (Edina, Minn. : ABDO Pub. Co., 2011)
Provides an overview of the history of the Dallas Cowboys football team, highlighting popular players, influential coaches, winning and losing seasons, and key moments that shaped the team and the NFL.
Champions at last -- From winless to America's team -- Falling on hard times -- The trade and the triplets -- Trying to get back -- Timeline -- Quick stats -- Quotes and anecdotes -- Glossary -- For more information -- Index -- About the author.
"SportsZone by ABDO Publishing Company"--P. [4] of cover.
Includes bibliographical references (p. 47) and index.
Keywords: Dallas Cowboys (Football team) -- History -- Juvenile literature; JUVENILE NONFICTION / Sports & Recreation / Football; Electronic books